RESIDUES OF SOME ORGANOCHLORINE PESTICIDES IN HUMAN BLOOD IN THE FADASI AREA, SUDAN - Sobair, Manal Eltom; Elzorgani, Gaafer A.; Almagzoub, Mohi El Din (Gezira Journal of Health Sciences, 2006)
Introduction: For many years, organochlorine pesticides (OCPs) have been of interest, because of their toxicity and high persistence .In developing countries, (OCPs) were used in large quantities to control agricultural pests and vectors of endemic diseases. In Sudan (OCPs) were restricted to public health purposes in 1981.  Objective: This study was conducted to asses the residue levels in the human blood. Methodology: A randomized population sample from Fadasi Village, which is located in a rural area where pesticides have been used for over 35 years were examined.   Result and Discusion: Analysis of human blood revealed the presence of  HCH, aldrin, heptachlor epoxide and DDE in varying concentrations. Statistical correlation was found to exist between the pesticide concentration and age, weight and duration of exposure. DDE was present in high concentrations, ranging between 0.38  6.88 ppm.